## Simplifying expressions

These laws can be used to simplify algebraic expressions.

#### Example 6

Simplify each expression by expanding brackets, and then adding and subtracting like terms.

Expression | Simplified expression |
---|---|

\(5x+7x\) | \(12x\) |

\(2x-y+3x\) | \(5x-y\) |

\(2x-3(y-x)\) | \(2x-3y+3x=5x-3y\) |

\(3(2x-5)+5x\) | \(6x-15+5x=11x-15\) |

\(7(z+6)-2(3z+4)\) | \(7z+42-6z-8=z+34\) |

\(8(q-5)-2(q+3)\) | \(8q-40-2q-6=6q-46\) |

\(x(x-5)+x(x+y)\) | \(x^2-5x+x^2+xy=2x^2-5x+xy\) |